Physical fitness evaluation of Paralympic winter sports sitting athletes - Bernardi, M.; Carucci, S.; Faiola, F.; Egidi, F.; Marini, C.; Castellano, V.; Faina, M. (Clinical Journal of Sport Medicine, 2012)
Objective To provide normative values of physical fitness in Paralympic winter sports athletes competing in a sitting posture and to identify the components relevant for successful performance.